دراسة تأثير مدة تطبيق ضماد ماءات الكالسيوم على التسرب الحفافي الذروي (دراسة مخبرية) - سليم, باسم; الخضر, تميم (Latakia University Journal -Medical Sciences Series, 2017)
الهدف : يهدف هذا البحث إلى دراسة تأثير الفترة الزمنية لتطبيق ضماد ماءات الكالسيوم على حدوث التسرب الحفافي الذروي بعد إجراء الحشو النهائي للقناة الجذرية.المواد والطرق : تألفت عينة البحث من 80 سناً بشرية, مقلوعة حديثاً ووحيدة القناة الجذرية, , حُضرت الأقنية الجذرية يدوياً , قسمت العينة عشوائياً إلى أربع مجموعات رئيسية كل مجموعة تتألف من 20 سناً. المجموعة (A) لا يطبق فيها الضماد, المجموعات D,C,B) ) تم تطبيق ضماد ماءات الكالسيوم فيها وبفترات زمنية مختلفة ( 30,14,7 يوماً ) على الترتيب. قسمت المجموعات D,C,B) ) عشوائياً لمجموعتين كل منها تتألف من 10 أسنان , وتمت إزالة الضماد بطريقتين, الأولى: بإجراء غسل بالماء المقطر ثم التجفيف بالأقماع الورقية فقط. الثانية: إجراء الغسل والتجفيف إضافة لإجراء حركة برد بسيطة للقناة بالمبرد (# 40). حشيت الأقنية الجذرية بطريقة التكثيف الجانبي باستخدام أقماع الكوتابيركا و أكسيد الزنك والأوجينول, وختمت فوهات الأقنية بالاسمنت الزجاجي الشاردي. حفظت العينات ضمن وعاد يحوي أزرق الميتيلين 2% بدرجة حرارة 37ْ مئوية لمدة 7أيام. تم شطر الجذور طولياً وتمت دراسة التسرب تحت المجهر ذو العدسة المجسمة وبتكبير( x20) . النتائج: أظهرت نتائج البحث أن تطبيق الضماد أدى لانخفاض متوسط التسرب الحفافي الذروي مقارنة مع عدم تطبيقه, وأن أفضل فترة لتطبيق الضماد هي 30 يوم و الفارق هام إحصائياً كما أن إزالة الضماد بالغسل والتجفيف فقط أعطى نتائج أفضل من حيث متوسط التسرب مقارنة مع إجراء التحضير البسيط بالقياس (#40) وذلك عند (p<0.05).الاستنتاجات : يمكننا الاستنتاج وفق الشروط التي أنجز فيها هذا البحث أن زيادة الفترة الزمنية لتطبيق ضماد ماءات الكالسيوم سيقلل من حدوث التسرب الحفافي الذروي وأن إزالة الضماد بالتجفيف والغسل فقط قبل الحشو النهائي أدى لانخفاض متوسط التسرب مقارنة مع إجراء حركات برد بسيطة بالقياس (#40).Aim: The aim of this study was to detect the effect of dressing period of calcium hydroxide medicament on the apical marginal leakage after obturation of root canal system.Materials and Methods: 80 freshly extracted single rooted human teeth were selected ,all the root canals were hand-instrumented. They were randomly divided into four groups of 20 teeth each. Group A has no intracanal medicament , groups (B,C,D) were dressed with Ca(OH)2 paste for a different periods of time (7,14,30) days respectively, groups (B,C,D) were divided into subgroups of 10 teeth according to removing of dressing . The removal of ca(OH)2was done by two ways, 1- By irrigating with distilled water and drying with paper points . 2- Size 40 k-file was used in slightly filing motion up to the working length then irrigated with distilled water and drying with paper points. After that all groups were obturated with lateral compaction technique using gutta-percha points and zinc oxide-eugenol cement. Then the access was sealed with GIC cement. The teeth were immersed into 2% mythylene blue solution ,The specimens were placed in an incubator at 37ْC ,with moisture at 100%, for 7 days .After that the roots were sectioned longitudinally and examined with stereomicroscope and liner leakage was measured .Results : The results showed that the leakage in Ca(OH)2 groups was significantly less than control group and the best period was 30 days, and the leakage was significantly less when the dressing was removed by irrigation with distilled water and drying using paper points than removal of dressing using last apical file (#40) in filling motion . (p<0,05)Conclusions : Under the conditions of this study, it can be concluded that increasing the period of dressing of ca(oh)2 led to decrease the marginal apical leakage and removal of dressing by irrigating and draying was resulted in less leakage.